Kajian Pelaksanaan Dana Alokasi Khusus Bidang Pendidikan - JM Tedjawati (Jurnal Pendidikan dan Kebudayaan, 2011)
The purpose of this analys is to obtain information about the implementation of Special Allocation Fund (DAK) in education, in: 1) Mechanism DAK planning of Local Government; 2) channeling mechanism of DAK from Local Government; 3) Realization of DAK; 4) Implementation of monitoring and evaluation; and 5) The opinion on the administration of the DAK. The findings of this analysis are: 1) The procedure of planning implementation of DAK has made education service districts/cities in accordance with the provision of technical guidance; 2) The distribution of DAK in accordance with the procedure through three stages; 3) In some districts/cities in 2010 the implementation of DAK experience delays because of changes in the implementation of self-managed way into the auction process; 4) Monitoring and evaluation conducted by the education office DAK district/city, but checks/audits conducted by the Inspectorate General of Ministry of National Education and the Regional Monitoring Agency (BAWASDA); 5) DAK self-managed way is considered more beneficial for the schools because of the use of DAK is more flexible than an auction company that conducted the auction winner.